COVID-19 Pandemic: Impact of the pandemic on individuals on the Autistic Spectrum (Research, Society and Development, 2022)
The COVID-19 pandemic brought several changes in our daily life, however, some groups suffered the impact even more, among them we can highlight people with autism spectrum disorder. The present review proposes to describe the impacts on individuals with ASD during the SARS-CoV-2 pandemic and how this affects their neuropsychological development, as well as the obstacles faced by them and their families. There are few studies that address this issue, besides being a recent subject, it is little addressed, thus, the present study is a systematic literature review, integrative and qualitative type, of publications from 2006 to 2021. A survey was carried out in the PubMed, SciELO, BVS, ERIC and DeCs databases. It was noticed that this group of individuals was affected in a specific and differentiated way, once they had the support of psychologists, educators and doctors, besides having abrupt changes in their life routines.